Neutrophil Extracellular Traps of Cynoglossus semilaevis: Production Characteristics and Antibacterial Effect - Zhao, Ming-li; Chi, Heng; Sun, Li (Frontiers in Immunology, 2017)
Neutrophil extracellular traps (NETs) are structures released by neutrophils as a cellular immune defense against microbial invasion. The process of NETs generation, netosis (NETosis), can take place via either a suicidal mechanism, during which the NETs-releasing cells became dead, or a “live” mechanism, during which the NETs-releasing cells remain vital. NETosis has been studied intensively in mammals in recent years, but very little is known about the NETosis in fish. In this study, we examined NETosis in tongue sole (Cynoglossus semilaevis), a species of teleost with important economic values. We found that following stimulation with phorbol 12-myristate 13-acetate (PMA) and three common fish bacterial pathogens, abundant NETs structures were released by neutrophils that were most likely in a live state. The released NETs captured, but did not kill, the bacterial pathogens; however, the replication of extracellular, but not intracellular, pathogens was inhibited by NETs to significant extents. Reactive oxygen species (ROS), nitric oxide (NO), and myeloperoxidase (MPO) production were observed to be enhanced in NETosing neutrophils, and blocking the production of these factors by inhibitors significantly decreased NETs production induced by PMA and all three bacteria. Taken together, these results indicate for the first time that in teleost there exists a non-cell death pathway of NETosis that produces NETs with antibacterial effects in a ROS-, NO-, and MPO-dependent manner.